2022
DOI: 10.2147/ppa.s348132
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and its Predictors among College Students in Addis Ababa, Ethiopia, 2021: A Cross-Sectional Survey

Abstract: Background:The coronavirus disease pandemic disrupted the normal social and economic activities of the people resulting in over 3 million deaths worldwide. Piece of literature depicted that predictors of vaccine acceptance are complex, multiple, and vary depending on the type of vaccine involved. Objective:The study aimed at assessing the COVID-19 acceptance and its predictors among college students in Addis Ababa, Ethiopia, 2021. Methods: A multi-center-institutional-based cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Accordingly, the acceptance of the COVID-19 vaccine for this study was found 60.3% at 95% of CI (55.5, 64.2). The finding was found in agreement with study conducted in Gurage Zone of Ethiopia 62.6%, 45 and higher than a studies conducted in Addis Ababa 40%, 24 among healthcare providers in Southwestern Ethiopia 48.4%, 23 and from the study conducted among the community in Wolaita Sodo of Ethiopia 45.5%. 11 The possible reason for having a high acceptance rate of the COVID-19 vaccine compared to the above-mentioned studies could be due to time and enhancement of awareness about the vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, the acceptance of the COVID-19 vaccine for this study was found 60.3% at 95% of CI (55.5, 64.2). The finding was found in agreement with study conducted in Gurage Zone of Ethiopia 62.6%, 45 and higher than a studies conducted in Addis Ababa 40%, 24 among healthcare providers in Southwestern Ethiopia 48.4%, 23 and from the study conducted among the community in Wolaita Sodo of Ethiopia 45.5%. 11 The possible reason for having a high acceptance rate of the COVID-19 vaccine compared to the above-mentioned studies could be due to time and enhancement of awareness about the vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…21 Studies conducted in Ethiopia also showed that there is hesitation to receive COVID-19 vaccines. 11,13,[22][23][24] The hesitation to receive the COVID-19 vaccine was also found in health care providers that will be a major obstacle for enhancing the vaccination coverage. 22,23,25 A survey of Addis Ababa inhabitants found that more over half of those polled had an unfavorable view regarding COVID-19 and its preventative measures.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19-related level of knowledge and attitude was found to determine vaccine acceptance. Eight studies [ 13 , 20 , 26 , 30 , [33] , [34] , [35] , 37 ] (I 2 = 93.9%, p = 0.000, Egger’s p = 0.758), revealed that good level of COVID-19 related knowledge predicted vaccine acceptance ((coff. (1.01 (0.85, 1.17))) [OR: 2.7, 95% CI: 2.3, 3.2]).…”
Section: Resultsmentioning
confidence: 99%
“…Studies identified that acceptance, intention, and willingness to get vaccinated significantly varied between the sex of respondents [ 13 , 15 , 17 , 19 , 20 , [23] , [24] , [25] , [26] , [27] ]. Also, some studies identified that a higher perceived level of COVID-19 risk positively contributed to the acceptance [ 23 , [28] , [29] , [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…All articles were cross-sectional and conducted in Ethiopia. The studies were distributed in southern region [ 21 , 27 29 , 31 ], Addis Ababa [ 22 24 , 36 ], Amhara region [ 25 , 26 , 30 , 33 , 37 ], and online or telephone. [ 32 , 34 , 35 , 38 ].…”
Section: Resultsmentioning
confidence: 99%